The relationship between hypoxia and Alzheimer’s disease: an updated review - Tao, Borui; Gong, Wei; Xu, Chengyuan; Ma, Zhihui; Mei, Jinyu; Chen, Ming (Frontiers in Aging Neuroscience, 2024)
Alzheimer's disease (AD) is one of the most common neurodegenerative diseases, and the most prevalent form of dementia. The main hallmarks for the diagnosis of AD are extracellular amyloid-beta (Aβ) plaque deposition and intracellular accumulation of highly hyperphosphorylated Tau protein as neurofibrillary tangles. The brain consumes more oxygen than any other organs, so it is more easily to be affected by hypoxia. Hypoxia has long been recognized as one of the possible causes of AD and other neurodegenerative diseases, but the exact mechanism has not been clarified. In this review, we will elucidate the connection between HIF-1α and AD, including its contribution to AD and its possible protective effects. Additionally, we will discuss the relationship between oxidative stress and AD as evidence show that oxidative stress acts on AD-related pathogenic factors such as mitochondrial dysfunction, Aβ deposition, inflammation, etc. Currently, there is no cure for AD. Given the close association between hypoxia, oxidative stress, and AD, along with current research on the protective effects of antioxidants against AD, we speculate that antioxidants could be a potential therapeutic approach for AD and worth further study.Alzheimer's disease (AD) is one of the most common neurodegenerative diseases, and the most prevalent form of dementia. It usually manifests as a gradual decline in episodic memory and cognitive abilities, leading to impairments in language, visuospatial skills, and often behavioral disturbances like apathy, aggression, and depression[1] [2]. The main neuropathological criteria for the diagnosis of AD are extracellular amyloid-beta (Aβ) plaque deposition and intracellular accumulation of highly hyperphosphorylated Tau protein as neurofibrillary tangles[3]. As the population ages, the incidence of AD continues to rise[4]. According to Alzheimer's Disease International the prevalence of dementia is about 50 million people